Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd002249.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oral anti-oestrogens and medical adjuncts for subfertility associated with anovulation

Abstract: Editorial group: Cochrane Menstrual Disorders and Subfertility Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 4, 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Although several approaches are available to induce ovulation in anovulatory PCOS women [3], clomiphene citrate (CC) is still considered the first-line therapy, with lower risk of adverse effects and lower cost [4]. However, evidence has demonstrated that approximately 15–40% of PCOS patients do not respond to CC treatment [5,6], which is termed CC resistance. It has been reported that PCOS women with obesity, hyperandrogenism, and insulin resistance are less likely to respond to CC, suggesting these factors could be prominent causes of CC resistance [79].…”
Section: Introductionmentioning
confidence: 99%
“…Although several approaches are available to induce ovulation in anovulatory PCOS women [3], clomiphene citrate (CC) is still considered the first-line therapy, with lower risk of adverse effects and lower cost [4]. However, evidence has demonstrated that approximately 15–40% of PCOS patients do not respond to CC treatment [5,6], which is termed CC resistance. It has been reported that PCOS women with obesity, hyperandrogenism, and insulin resistance are less likely to respond to CC, suggesting these factors could be prominent causes of CC resistance [79].…”
Section: Introductionmentioning
confidence: 99%
“…Given its ability to induce ovulation in oligo-ovulatory and anovulatory females, CC is considered a first-line medical approach to improve fertility in this patient population (3)(4)(5). Hammond et al (6) demonstrated that, in a group of anovulatory and oligomenorrheic women treated with CC, 86% ovulated and 49% of those patients conceived.…”
mentioning
confidence: 99%
“…More recently, in a compilation of seven published studies looking at CC and ovulation, Homburg (7) reported an ovulation rate of 73% with a pregnancy rate (PR) of 36%. In addition, Beck et al (5) analyzed 12 randomized controlled trials regarding oral antiestrogen treatment in patients with anovulatory infertility and concluded that CC is effective in increasing the PR when compared with placebo. Thus, CC effectively stimulates both ovulation and greatly improves fertility success in most anovulatory women.…”
mentioning
confidence: 99%
“…A recent systematic review shows evidence supporting the effectiveness of the current first-line treatment CC. There was no evidence of a difference in effect between CC and TMX [4,7,15] . No review describing adverse effects of CC in infertility patients has been published in the literature.…”
Section: Ovulation Induction and Selective Estrogen Receptor Modulatorsmentioning
confidence: 76%